2009
DOI: 10.1093/jxb/erp267
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and proteomic analysis of ‘Dixiland’ peach fruit (Prunus persica) upon heat treatment

Abstract: Shipping of peaches to distant markets and storage require low temperature; however, cold storage affects fruit quality causing physiological disorders collectively termed 'chilling injury' (CI). In order to ameliorate CI, different strategies have been applied before cold storage; among them heat treatment (HT) has been widely used. In this work, the effect of HT on peach fruit quality as well as on carbon metabolism was evaluated. When fruit were exposed to 39 degrees C for 3 d, ripening was delayed, with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 76 publications
7
76
0
3
Order By: Relevance
“…The 2-DE gels from mango protein extracts showed good resolution, and the number of detected spots in our study was similar to those of other previous proteomic studies on climacteric fruits using the same technology [10,16,17]. Similarly, the number of variable spots identified in ripening mango was close to those reported in other fruits [16,18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The 2-DE gels from mango protein extracts showed good resolution, and the number of detected spots in our study was similar to those of other previous proteomic studies on climacteric fruits using the same technology [10,16,17]. Similarly, the number of variable spots identified in ripening mango was close to those reported in other fruits [16,18].…”
Section: Discussionsupporting
confidence: 88%
“…The 2-DE gels from mango protein extracts showed good resolution, and the number of detected spots in our study was similar to those of other previous proteomic studies on climacteric fruits using the same technology [10,16,17]. Similarly, the number of variable spots identified in ripening mango was close to those reported in other fruits [16,18]. According to the PCA, the variable spots detected were clearly correlated to the ripening stage, and although the unripe sample from experiment C was slightly different, the samples from the group of climacteric material were much more similar and set apart from the preclimacteric ones in the score plot, which corroborates the physicochemical data presented in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies, the proteomic changes associated with ripening were assessed in Dixiland peach fruit (Lara et al, 2009), and later, in five different peach varieties, in order to find out common proteomic changes in different peach varieties (Nilo, Campos-Vargas, & Orellana, 2012). The results indicated that the proteome is conserved among varieties and, also, during the transition from a firm to a soft fruit, which was associated with the narrow genetic background of the commercial peach varieties (Nilo et al, 2012).…”
Section: Metabolite Changes Associated With Peach Post-harvest Ripenimentioning
confidence: 99%
“…Given that the proteome is closer to the fruit phenotype than is the genome or the transcriptome along with the fact that it is more directly responsive to environmental stimuli (Chan, 2012), proteomic analysis provides a comprehensive view of fruit's adaptation to different environments. Almost all past proteomic studies of peach fruit were focused on mesocarp tissue (Lara et al, 2009; Nilo et al, 2010, 2012; Hu et al, 2011; Prinsi et al, 2011; Zhang et al, 2011; Giraldo et al, 2012); whereas research concerning skin proeome as an isolated component during peach ripening have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%